Cultural aspects of Malaysian English and Russian medical profession names - Lenart, Istvan; Buvalin, Nick (Penerbit Universiti Kebangsaan Malaysia, 2020)
The translation of medical profession names may challenge even the most experienced translator. Selecting the appropriate equivalents is not always evident: the English term dentist for instance may correspond to either стоматолог [stəmɐtˈolək] (“mouth expert”) or зубной врач [zʊbnˈoj vrˈatɕ] (“tooth doctor”) or дантист [dɐntˈist] (“dental hygienist”) in the Russian language. A physiotherapist can be translated as физиотерапевт [fɪzɪɐtɪrɐpˈevt]; however a physiotherapist in Russia must necessarily hold a medical doctor degree, in contrast with the practice of most Anglo-Saxon countries. Although the compared terms are often considered as equivalents by bilingual dictionaries (e.g.: surgeon and хирург [xɪrˈurk]) (Buvalin and Lenart 2017); however, their denotations and connotations may significantly differ, thus their improper translation may lead to intercultural misunderstandings. In this paper, 17 pairs of English-Russian medical profession names were investigated – the English lexemes coming from the Malaysian variety of the English language – with two competing linguistic methods: the association experiment and a corpus linguistic approach. The authors aimed at identifying semantic dissimilarities between the Malaysian English and the Russian lexemes in a cross-cultural context, from the perspective of both the association experiment and corpus linguistic methods. Firstly, a questionnaire-based association experiment was conducted with 300 Russian and 50 Malaysian medical university students, followed by a contrastive corpus linguistic analysis relying on the Russian National Corpus and the NOW (News on the Web) corpus. Results of the cross-cultural investigation revealed substantial semantic differences between the English and Russian profession names, as well as confirmed the complementary character of the association experiment and the corpus linguistic methods.